PENANGANAN KONFLIK LALULINTAS DI PERSIMPANGAN GATOT SUBROTO- GEDUNG EMPAT CIMAHI - Natalia Tanan (Jurnal Jalan-Jembatan, 2008)
Intersection is the potential point of traffic conflict because of the growth and the mixing of traffic. The existence of conflict data collection will help to identify the cause of the accident at intersection. One of the effort that has been done in order to improve the road safety is: Full scale implementation of road safety feature at Gatot Subroto – Gedung Empat Intersection, Kota Cimahi. The implementation done based on conflict data on the location. The activities are: the making of traffic island, angkot lane, priority sign, stop sign, the improvement of shoulder and facilities for pedestrians. To analyze the effectivess of handling, before-after method was used. In this pape, 5 (five) types of coflicts on 8 points (T1, T2, T3, T4, T5, T6, T7, andT8) were identified.The result showed that after handling, there were significant conflict reductions at points T1, T2, T6, T7, and T8. But there were no conflict reductions after handling at points T3, T4, and T5. After handling, generally there were reduction of total traffic conflict at Gatot Subroto – Gedung Empat Intersection by142,2 conflicts/1000 vehicles to 82,07 conflicts/1000 vehicles. Keywords: intersection, traffic conflict, before-after analysis